The removal of nitrogen using an autotrophic hybrid hollow-fiber membrane biofilm reactor - Shin, JH; Sang, BI; Chung, YC; Choung, YK (ELSEVIER, 2005)
A hollow-fiber membrane biofilm reactor (HF-MBfR) treating nitrogen in synthetic wastewater was studied in respect to nitrification and dertitrification ability using autotrophic microorganism over a period of 260 days. The hybrid HF-MBfR system consists of a nitrification HF-MBfR and denitrification HF-MBFR. Oxygen and hydrogen were supplied through the lumen of fibers as electron acceptor and donor. In Phase 1, two HF-MBtR were operated separately during the period of 149 days. And then, the HF-MBfR were operated by hybrid system that is connected continuously. The hybrid HF-MBfR was operated at hydraulic retention time (HRT) of 4 h, 2 h, and the volumetric NH4+-N loading rate increased from 0.42 to 1.28 kgNH(4)(+)-N/m(3)d by increasing NH4+-N concentration of influent from 150 to 200 mgN/L. The average total nitrogen removal efficiency was above 98% during the experiment steps and the maximum volumetric total nitrogen removal rate was 1.20 kgN/m(3)d in the hybrid HF-MBfR system. In this study, the results suggested that this hybrid HF-MBfR system operated effectively for nitrogen removal in an inorganic environment and can be used stably as a high rate nitrogen removal technology.
Keywords: NITRATE REMOVAL; DENITRIFICATION; NITRIFICATION